Trends in the Use of Creative Thinking Skills in Physics Education (2015-2024): A Systematic Literature Review - Sul Daeng Naba; Heru Kuswanto; Aris Kurniawan; Nanang Adrianto (Berkala Ilmiah Pendidikan Fisika, 2026)
This study aims to investigate the trends and efforts to enhance creative thinking skills in physics education through a systematic literature review (SLR). While various instructional models have been implemented, empirical evidence regarding creative thinking in the Indonesian physics context remains fragmented, and previous reviews often lack a specific focus on national indexing trends. Adhering to the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) framework, this study systematically screened articles from the Science and Technology Index (SINTA) database. The selection process used the search string 'creative thinking skills in physics education' and was guided by five inclusion criteria: SINTA 2-4 indexing, a publication timeframe of 2015-2024, a focus on creative thinking as the primary construct, journal article format, and open access availability. From an initial identification of 91 articles, the screening and eligibility stages based on titles, abstracts, and content suitability resulted in a final set of 51 analyzed articles. The findings indicate that the Project-Based Learning (PjBL) model (27%) and Problem-Based Learning (PBL) model (25%) were the most predominant strategies used to foster creative thinking. Quantitative methods with quasi-experimental designs emerged as the most frequently employed research approach (41%), reflecting a strong emphasis on empirical validation. Research peaked in 2023 with 14 publications, with 'Temperature and Heat' being the most investigated topic among Grade 10 students. This study contributes a strategic roadmap for educators to implement innovative models and identifies a need for more qualitative insights into the creative processes in physics education.